2000
DOI: 10.1562/0031-8655(2000)072<0625:eosote>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Solvent on the Excited-state Photophysical Properties of Curcumin¶

Abstract: Photophysical properties of curcumin, 1,7-bis-(4-hydroxy-3-methoxy phenyl)-1,6-heptadiene-2,5-dione, a pigment found in the rhizomes of Curcuma longa (turmeric) have been studied in different kinds of organic solvent and also in Triton X-100 aqueous micellar media using time-resolved fluorescence and transient absorption techniques having pico and nanosecond time resolution, in addition to steady-state absorption and fluorescence spectroscopic techniques. Steady-state absorption and fluorescence characteristic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
205
0
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 226 publications
(229 citation statements)
references
References 22 publications
22
205
0
2
Order By: Relevance
“…It appears that the fast ESIHT times observed in these micelles compare well with those in the nonpolar solvent cyclohexane. 21,22 However, as indicated earlier, the ESIHT process of curcumin in cyclohexane is most likely faster than what was measured with TCSPC due to limited temporal resolution. In comparison to curcumin in the TX-100 micelle, the ESIHT process occurs faster in the DTAB and SDS micelles.…”
Section: Uv-vis Absorption and Emission Spectra Of Curcumin In Micellesmentioning
confidence: 76%
See 2 more Smart Citations
“…It appears that the fast ESIHT times observed in these micelles compare well with those in the nonpolar solvent cyclohexane. 21,22 However, as indicated earlier, the ESIHT process of curcumin in cyclohexane is most likely faster than what was measured with TCSPC due to limited temporal resolution. In comparison to curcumin in the TX-100 micelle, the ESIHT process occurs faster in the DTAB and SDS micelles.…”
Section: Uv-vis Absorption and Emission Spectra Of Curcumin In Micellesmentioning
confidence: 76%
“…[21][22][23] Nardo et al and Khopde et al independently reported that there is a ∼50 ps decay component in the fluorescence lifetime (89 and 64 ps, as measured by the two groups, respectively) of curcumin in cyclohexane using TCSPC. 21,22 This decay component is, however, limited by the time resolution of the TCSPC apparatus.…”
Section: Uv-vis Absorption and Emission Spectra Of Curcumin In Micellesmentioning
confidence: 96%
See 1 more Smart Citation
“…In addition to ESIHT, the fluorescence upconversion results also reveal that there is a short-lived component with a time scale of 12 ps in methanol, which is likely to be undetectable in TCSPC because of insufficient time resolution. Solvation, in addition to ESIHT, is expected to play a role in the excited-state relaxation dynamics due to the significant dipole moment change reported for curcumin: ∆µ ) 6.1 D. 31 Such a ∆µ is comparable to that of Coumarin 153 (∆µ ≈ 8 D), 42,49 which is a standard probe molecule for solvation dynamics. Additionally the fluorescence spectra exhibit a Stokes shift that is largely dependent on solvent polarity, implying that solvation may play a major role in the relaxation of the excited state in addition to ESIHT.…”
Section: Resultsmentioning
confidence: 99%
“…12,[31][32][33][34] In all cases, these studies focused on excited-state intramolecular hydrogen atom transfer (ESIHT) of curcumin because this phenomenon has been associated with the medicinal properties of other pigment molecules, including hypericin and hypocrellin. [35][36][37][38][39] Two of these studies agree that the fluorescence lifetime of curcumin in methanol has a dominant component with a time constant of roughly 130 ps.…”
Section: Introductionmentioning
confidence: 99%